2015
DOI: 10.12738/estp.2015.3.2606
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Dissertation Process within the Framework of Flow Theory: A Qualitative Study

Abstract: The purpose of this study is to examine the flow of doctoral students who are also research assistants and in the dissertation process. The study was designed using the case study method. The case undertaken in the study was the dissertation process. Eleven participants were selected into the study using maximum variation sampling. Face-to-face, semi-structured interviews were conducted with the participants. Descriptive analysis was used to analyze the transcripts. The descriptive analysis of the data identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Research has repeatedly demonstrated that the chair-candidate relationship was notably tied to academic success (Jaeger et al, 2011;Neale-McFall, & Ward, 2015). Moreover, findings indicated that problems with chair-candidate relationships were causes for candidates failing to attain the doctorate (Cakmak et al, 2015;Jaeger Sandmann, & Kim, 2011).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Research has repeatedly demonstrated that the chair-candidate relationship was notably tied to academic success (Jaeger et al, 2011;Neale-McFall, & Ward, 2015). Moreover, findings indicated that problems with chair-candidate relationships were causes for candidates failing to attain the doctorate (Cakmak et al, 2015;Jaeger Sandmann, & Kim, 2011).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…According to Burkard (2014), the devotion, time commitment, and personal effort needed to write a doctoral dissertation is too much. Doctoral candidates confront numerous problems along the path to completing the dissertation (Blum, 2010;Cakmak et al, 2015;Barrett & Hussey, 2015). The typical problems include: synthesization of information, conceptualization in writing, clarification of the links between the parts and the whole, decision on an appropriate voice, and completion of the paper.…”
Section: Writing the Dissertationmentioning
confidence: 99%
See 3 more Smart Citations